2018
DOI: 10.1152/jn.00589.2017
|View full text |Cite
|
Sign up to set email alerts
|

Decreased spontaneous electrical activity in neuronal networks exposed to radiofrequency 1,800 MHz signals

Abstract: So far, the only identified biological effects of radiofrequency fields (RF) are known to be caused by heating but the issue of potential nonthermal biological effects, especially on the central nervous system (CNS), remains open. We previously reported a decrease in the firing and bursting rates of neuronal cultures exposed to a Global System for Mobile (GSM) RF field at 1800 MHz for 3 min (Moretti et al. 2013). The aim of the present work was to assess the dose-response relationship for this effect, and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Besides, it has been revealed that RF-EMF exposure causes neural behavior changes in rats and mice, such as influenced emotional behavior, decreased locomotor activities, and impairment of cognitive functions (Zhang et al, 2017;Kim et al, 2019b). RF-EMF exposure also influenced the electrical activity in neuronal networks in the brain and peripheral neurons (El Khoueiry et al, 2018;Prucha et al, 2018). Recently, it has been found that prenatal RF-EMF exposure inhibits the proliferation and differentiation of embryonic neural stem cells (NSCs), which affects the neurological functions of adults (Kaplan et al, 2016;Eghlidospour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it has been revealed that RF-EMF exposure causes neural behavior changes in rats and mice, such as influenced emotional behavior, decreased locomotor activities, and impairment of cognitive functions (Zhang et al, 2017;Kim et al, 2019b). RF-EMF exposure also influenced the electrical activity in neuronal networks in the brain and peripheral neurons (El Khoueiry et al, 2018;Prucha et al, 2018). Recently, it has been found that prenatal RF-EMF exposure inhibits the proliferation and differentiation of embryonic neural stem cells (NSCs), which affects the neurological functions of adults (Kaplan et al, 2016;Eghlidospour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate that the scattering of microwave in the brain functional sites leads to the polarization and depolarization of the brain tissue cell fluid, resulting in the change in dielectric constant and conductivity, which in turn changes the characteristics of microwave scattering to achieve the purpose of imaging [ 19 ]. Some recent reports have addressed the fact that microwave scattering has a significant effect on resting state EEG, particularly on the fact that the power of the EEG increases in the alpha band [ 24 , 25 ]. Exposure to electromagnetic fields can cause changes in the sleep EEG power [ 26 ], thereby suggesting that electromagnetic waves may affect brain function and the recovery process involved in sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, other studies, like those mentioned above, have reported the effects with small temperature increase as non-thermal. For example, in the case of a decrease in spontaneous electrical activity in cultured cortical neurons during a short exposure to GSM 1800 MHz (15 min at SAR ranging from 0.01 to 9.2 W/kg), the authors also examined the in uence of bulk heating in the culture medium, and found that it caused increased burst activity 23 . Notably, the results showed an opposite effect with bulk heating versus RF-EMF exposure since RF-EMF resulted in decreased burst activity 23 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the case of a decrease in spontaneous electrical activity in cultured cortical neurons during a short exposure to GSM 1800 MHz (15 min at SAR ranging from 0.01 to 9.2 W/kg), the authors also examined the in uence of bulk heating in the culture medium, and found that it caused increased burst activity 23 . Notably, the results showed an opposite effect with bulk heating versus RF-EMF exposure since RF-EMF resulted in decreased burst activity 23 . In this experiment, the authors imitated the 0.7 °C temperature rise modeled for RF-EMF exposure (SAR of 9.2 W/kg) by subjecting the cortical neuronal cultures to 15-min heating in the incubator using a heat produced by an electric hotplate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation